(untitled) (Studia Prawnicze / The Legal Studies, 2023)
The article deals with current problems ensuing from the organization and legal regulation of employment relations in France. The following questions have been discussed in this connection: reforms to affect the structure of an enterprise, the participation of employees in the management and the division of profits, employment policy, improvement of working conditions. The provisions of the law that regulate the above problems have been pointed out and presented against a broad, socio-economic background. The attitudes towards particular issues assumed by the three main parties to the French employment relations (the state, patronage, employees represented by trade unions) have been specified and differences in opinion pertaining to the concepts in this respect and postulated measures to this end — emphasized. In this manner the author attempted at drawing a panorama of clue problems arising in the sphere of and ensuing from employment relations in France, as well as steps postulated and undertaken with a view to solving the discussed problems.